ANALYSIS OF THE IMPACT OF THE IMAM MODEL ON UNDERSTANDING, SKILLS AND INDEPENDENCE IN THE ENTREPRENEURSHIP COURSE - Mashudi, Imam; Darman; Meilan Matiti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
The challenge of higher education today is how graduates can have good intellectual abilities, have skills and be independent so that they can be absorbed in the world of work or even be able to create their own jobs. BPS data in 2024 recorded that the unemployment rate for higher education reached 5.25% (147,841,991) of the total population of Indonesia in 2024. This study aims to analyze the impact of the IMAM Model on understanding, skills, and independence in the context of entrepreneurship learning. The main issue raised was the effectiveness of the model in improving students' cognitive aspects, practical skills, and entrepreneurial attitudes. The method used is a quantitative approach with Structural Equation Modeling (SEM) analysis using Partial Least Squares (PLS). The results show that the IMAM Model has a significant effect on the understanding of the concept of entrepreneurship with a tcal value of 12.182 and a P Value of 0.000. In addition, this model also has a significant effect on practical skills in entrepreneurship with a tcal value of 5.866 and P Values of 0.000. Finally, the IMAM Model has been proven to have a significant effect on independence and entrepreneurial attitude with a tcal value of 13.833 and P Values of 0.000. These findings show that the application of the IMAM Model can improve students' entrepreneurial competence as a whole.